Environmentally biopreparation of selenium and zinc nanoparticles using Ginkgo biloba extract in preservation of edible oils - Ayman Y. El-Khateeb (Journal of Agriculture, Food and Environment, 2020)
This research was conducted to study the antioxidant activity of Ginkgo bilobaextract and the green synthesis of selenium and zinc nanoparticles with the bio-compatible extract of Ginkgo biloba. The structural and optical properties of nanoparticles showed that a spherical shapeof zinc with particle size ranged from 70.63 to 82.57 nm, and 52.89 and 66.47 nm for selenium. The HPLC tech-nique was used to identify the phenolic components of Ginkgo bilobaextract, it contained 15 polyphenol compounds. Ginkgo bilobaextract and synthetic nano-particles of selenium and zinc were added to corn and soybean oils at concentra-tions of 200, 400 and 800 ppm as natural antioxidants in comparison with TBHQ as synthetic. Rancimat time at 110°C indicated that the induction period of the control oils varied from 10.70 and 5.53 hours, respectively, for corn oil and soybean oil. Corn and soybean oils treated with selenium nanoparticles prepared with Ginkgo bilobaextract at a concentration of 800 ppm showed the highest stability times which were 12.5 and 23.9, respectively. Zinc nanoparti-cles of Ginkgo bilobaextract can involve with the bio-reduction reaction at a concentration of 800 ppm to prevent oxidation and rancidity of oils as indicated for 7.07 and 6.02 hours for oils corn and soybeans, respectively. Thus, the addi-tion of selenium and zinc nanoparticles of Ginkgo bilobaextract to corn and soybean oils has shown a positive effect on the oxidative and thermal stability of these raw materials and could be recommended as an alternative antioxidant in oils.